Analisis Dan Perancangan Aplikasi E-Donasi Berbasis Web Dengan Metode Software Development Life Cycle - Qoish Sirrusysyahid Al Qordhowi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The Al Qaaf Foundation still uses conventional and manual methods for recording, calculating, and reporting donations. This causes the donation process to be lengthy and several obstacles to arise, such as when searching for donor data. This e-donation application allows people to make donations online easily and quickly, without having to go to a physical location or send money directly. Therefore, the Software Development Life Cycle (SDLC) method is very necessary in the development of a web-based e-donation application so that it can produce a reliable, secure, and effective e-donation application. With this donation application, it is hoped that it can help the AL QAAF FOUNDATION overcome the obstacles and problems that occur in the donation process.